Sexism and Attitudes Toward Policy Spending in Australia and the United States - Beauregard, Katrine; Holman, Mirya; Sheppard, Jill (Frontiers in Political Science, 2022)
Sexist attitudes influence a wide range of political behaviors, including support for explicitly gendered policies like gender quotas. But we know much less about how sexism might broadly shape policy preferences. We argue that some policy domains are implicitly associated with being pro-women or pro-men because of gender socialization, gender segregation in the workforce, and differences in policy preferences in the general population and among political elites. As (hostile) sexists view women as inherently undeserving, making illegitimate claims on government, and getting ahead at the expense of men, we hypothesize that they will oppose policies associated with women, while supporting “male” policies such as defense and law enforcement. We test our hypothesis using the 2019 Australian Election Study and 2018 US Cooperative Congressional Study. We find similar patterns of policy preferences, wherein those holding sexist attitudes (net of other attitudes and demographic characteristics) want to cut funding for pro-women policies like social services, education, and health, while they approve of increased funding for law enforcement and defense.